2018
DOI: 10.1007/s00392-018-1336-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of cryoballoon ablation for the treatment of atrial fibrillation in elderly patients

Abstract: Our data strengthen the value of CB ablation for the treatment of AF as an effective and safe procedure in elderly patients, with similar success and complication rates when compared with a younger population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 23 publications
0
43
0
Order By: Relevance
“…First, CB‐A can reduce procedure time. According to previous reports, the efficacy of PVI with CB‐A might be comparable to that of PVI with RF‐CA in patients with AF greater than 75 years and may involve a shorter procedure time. Procedure and fluoroscopy times were comparable between the groups in this study population.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…First, CB‐A can reduce procedure time. According to previous reports, the efficacy of PVI with CB‐A might be comparable to that of PVI with RF‐CA in patients with AF greater than 75 years and may involve a shorter procedure time. Procedure and fluoroscopy times were comparable between the groups in this study population.…”
Section: Discussionmentioning
confidence: 86%
“…In this study, we found that the main finding is that CB‐A is a safe and effective procedure for the treatment of AF in patients ≥80 years, granting freedom from AF/AT recurrence in 86.8% of patients at 1 year after ablation. To our knowledge, although several reports have described the efficacy and safety of CB‐A in elderly patients greater than 75 years, our present study is the first to compare the efficacy and safety of CB‐A in patients aged ≥80 years with a cohort younger than 80 years.…”
Section: Discussionmentioning
confidence: 95%
“…Our results serve to extend and confirm those of a number of prior publications that have reported the outcomes of cryoballoon ablation in elderly patients with AF. [ 7 16 ] The definition of ‘elderly’ in these series included patients aged as young as 70 years, and the reported success rates range from 62 to 87%. In the aggregate, these studies have investigated safety and efficacy rates at 1 year in a total of 2,235 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Given the rising proportion of elderly patients with AF, the utilization of CA in elderly patients is growing. Numerous studies have investigated the outcomes of CA of AF in elderly patients, and the mean age of the included patients is variable [4][5][6][7][8][9][10][11][12][13] . To the best of our knowledge, ours is the first study from the US to compare the outcomes of CB vs. RF AF ablation in elderly patients.…”
Section: Discussionmentioning
confidence: 99%